Penerapan Metode Value Stream Mapping dan 5S untuk Meningkatkan Cycle Time Proses Produksi Sepatu pada UD. XYZ - Nando, Fiky Two; Ilmanzani, Latisha Aura; Yunanda, Fitrah; Permatasari, Shinta Naafia; Izulhaq, Muhammad Nabil; Bua, Febrianto Taruk (Yayasan Cendekia Gagayunan Indonesia, 2025)
UD. XYZ is one of the trading businesses that produces shoes with a simple working system. The production process is still dominated by activities that take a considerable amount of time due to the lack of standardized work and the high number of activities that do not directly add value to the product. This condition causes the total production time to be long and work efficiency to decrease. Therefore, this research aims to reduce cycle time and improve the efficiency of the shoe production process by identifying waste and applying Value Stream Mapping (VSM), Process Activity Mapping (PAM) methods, and implementing the 5S principles for improvement efforts. Based on the analysis results of the Current State Map and PAM, the total production time is 5,760 seconds, with most of it being necessary non-value added (NNVA) activities. After implementing improvement efforts using the 5S principles, the process and picking times, which previously took a long duration, were successfully reduced, resulting in a decrease in cycle time to 5,030 seconds, or an efficiency improvement of 12.6%. This result was achieved by adding supporting tools and machines and implementing improvements to the work system at UD. XYZ. Thus, the combination of the VSM method and the 5S principles proved effective as an improvement strategy for optimizing production performance.